The Pendulum Movement of Conflict, Gender, Environment, and Peacebuilding - Angulo Rincón, Lizandro (Revista Calarma, 2023)
The beginning of 2023 brought pendular news on conflict and peacebuilding, the subject of the dossier of the Calarma Journal Number 2. On the one end, the war between Ukraine and Russia, one of the most Global since World War II, commemorates a year of confrontation with 300,000 military and 18,000 civilian deaths (Maguey, 2023) caused by the bombings and the clash of the infantry between the sides in contention. Moreover, this is one of the 32 active conflicts disclosed by the Escola de Cultura de Pau of the Autonomous University of Barcelona in its 2021 report on conflicts, human rights, and peacebuilding (Navarro et al., 2022). It already reported the confrontation between the pro-Russian separatist militias in the Donetsk and Lugansk regions supported by Russia and the State Armed Forces under the new pro-European authorities, which hinted at where it was going to escalate, that is, to the war that the media show today.